I remember nothing : and other reflections - Ephron, Nora (New York : Knopf, 2010)
A humorous collection of personal essays discusses the author's career in journalism, divorce, a long-anticipated inheritance with unanticipated results, and the evolution of her relationship with her e-mail in-box.
Keywords: Ephron, Nora; Ephron, Nora; Middle-aged women -- Humor; American wit and humor; Middle aged women -- Humor; Wit and humor